Dialecto Literario and Regional Literature in the College Classroom: Salvador Salazar Arrué’s Cuentos de Barro (1933) - Cloonan Cortez, Denise (Colombian Applied Linguistics Journal, 2023)
Regional literature, specifically eye dialect, is conspicuously missing from language classrooms due to its non-normative orthography. Even native speakers of the language struggle with unconventional spellings as dictionaries become useless tools. Moreover, most readers lack intuition regarding regional speech phenomena or its orthographic representations. While we are all speakers of a dialect, many are only familiar with their regional variety. Salvadoran regional literature may feature “pue” instead of “pues”, “pos” in Mexican literature, and “po” in Chilean literature. All examples divert from the normative “pues” despite sharing the same contextual cues. In regional representations, “fue” is written as “jue” to convey the [ˈxwe] pronunciation of the word. These regional texts, like those written by Salvadoran author Salarrué, are extraordinarily interesting because they capture graphically the phonetic phenomena characteristic of languages in contact and/or dialectal variations such as elisions and aspirations, among others. In a study conducted by the researcher, it was found that heritage speakers of Spanish possess a unique background knowledge compared to native and non-native speakers. Along with linguistic decoding strategies, this proved to be beneficial for them when reading and understanding “Semos malos”. Heritage students (Group C) were able to ‘evaluate’ many types of ‘candidates’ and were well-equipped to understand global phonetic phenomena as portrayed in regional literature from other areas.